Self‐reported obstructive sleep apnea, amyloid and tau burden, and Alzheimer's disease time‐dependent progression. Issue 2 (8th October 2020) - Bubu, Omonigho M.; Umasabor‐Bubu, Ogie Q.; Turner, Arlener D; Parekh, Ankit; Mullins, Anna E.; Kam, Korey; Birckbichler, Madeline K.; Mukhtar, Fahad; Mbah, Alfred K; Williams, Natasha J.; Rapoport, David M.; de Leon, Mony; et al.
Abstract: Introduction: Obstructive sleep apnea (OSA) is associated with Alzheimer's disease (AD) biomarkers in cognitively normal (CN) and mild cognitive impaired (MCI) participants. However, independent and combined effects of OSA, amyloid beta (Aβ) and tau‐accumulation on AD time‐dependent progression risk is unclear. Methods: Study participants grouped by biomarker profile, as described by the A/T/N scheme, where "A" refers to aggregated Aβ, "T" aggregated tau, and "N" to neurodegeneration, included 258 CN (OSA‐positive [OSA+] [A+TN+ n = 10, A+/TN− n = 6, A−/TN+ n = 10, A−/TN− n = 6 and OSA‐negative [OSA‐] [A+TN+ n = 84, A+/TN− n = 11, A−/TN+ n = 96, A−/TN− n = 36]) and 785 MCI (OSA+ [A+TN+ n = 35, A+/TN− n = 15, A−/TN+ n = 25, A−/TN− n = 16] and OSA− [A+TN+ n = 388, A+/TN− n = 28, A−/TN+ n = 164, A−/TN− n = 114]) older‐adults from the Alzheimer's Disease Neuroimaging Initiative cohort. Cox proportional hazards regression models estimated the relative hazard of progression from CN‐to‐MCI and MCI‐to‐AD, among baseline OSA CN and MCI patients, respectively. Multi‐level logistic mixed‐effects models with random intercept and slope investigated the synergistic associations of self‐reported OSA, Aβ, and tau burden with prospective cognitive decline. Results: Independent of TN‐status (CN and MCI), OSA+/Aβ+ participants were approximately two to four times more likely to progress to MCI/AD ( P < .001) and progressed 6 to 18 months earlier ( P < .001), compared to other participants combined (ie, OSA+/Aβ−, OSA−/Aβ+, and OSA−/Aβ−). Notably, OSA+/Aβ− versus OSA−/Aβ− (CN and MCI) and OSA+/TN− versus OSA−/TN− (CN) participants showed no difference in the risk and time‐to‐MCI/AD progression. Mixed effects models demonstrated OSA synergism with Aβ (CN and MCI [β = 1.13, 95% confidence interval (CI), 0.74 to 1.52, and β = 1.18, 95%CI, 0.82 to 1.54]) respectively, and with tau (MCI [β = 1.31, 95% CI, 0.87 to 1.47]), P < .001 for all. Discussion: OSA acts in synergism with Aβ and with tau, and all three acting together result in synergistic neurodegenerative mechanisms especially as Aβ and tau accumulation becomes increasingly abnormal, thus leading to shorter progression time to MCI/AD in CN and MCI‐OSA patients, respectively.